HINDRANCE OF WOMEN AS ENTREPRENEUR - Devi, R.Radhika; Devika, V. (International Journal of Psychosocial Rehabilitation, 2020)
Today, Women entrepreneurs have their own opinion, are self-assured, able to withstand all risk and are efficient managers. In spite of dual responsibilities, several women plan their lives very skillfully and succeed in filling these dual roles in a smooth way. The experience gained outside her home enables her to enrich family relationships through new outlook on tradition in a changing world. By continuously seeking connection with the world of science and culture, she can become a better organizer and help to promote growth. Blessed with these qualities and creative urges women can contribute significantly to economic productivity of the nation. They can take lead in bringing ethics in business and human approach in social economic relation and make this world a better place to live. Though women represent almost half the humanity, their contribution to leadership and management is much less. Time has come for women to come out of the drudgery of house work and give vent to their creativity and entrepreneurship.